Real-Time Threshold-Based Fall Detection System Using Wearable IoT - Amir N.I.M.; Dziyauddin R.A.; Mohamed N.; Ismail N.S.N.; Zulkifli N.S.A.; Din N.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Internet of things; Wearable technology; ADXL 335; Condition; Detection system; Fall detection; Fall detection system; IoT; Real- time; Threshold methods; Time thresholds; Wearable devices; Fall detection